PEMBELAJARAN TREFFINGER BERBANTUAN PERMAINAN TRADISIONAL CONGKLAK UNTUK MENINGKATKAN KEMAMPUAN KOMUNIKASI MATEMATIS - Ulya, Himmatul; Rahayu, Ratri (UNIVERSITAS MUHAMMADIYAH METRO, 2017)
Mathematics learning in SD 1 Bae Kudus could not make students fun in learning yet. Mathematics learning was still centered on the teacher so that students had not had the opportunities to convey their mathematical ideas either orally or written. This caused the students’ mathematical communication ability were low. The goals of this study were: (1) to determine whether the mathematical communication ability of students through the application of treffinger learning using a traditional game of congklak on multiplication material reach the completeness learning and (2) to determine the quality improvement of students’ mathematical communication ability who joined treffinger learning using a traditional game of congklak on multiplication material. This study was an experimental research with one-group pretest-posttest design. The research implemented on 2nd grade ini SD 1 Bae Kudus in multiplication material. The techniques of data collection used was test to measure mathematical communication ability of students. The techniques of data analysis in the study included the analysis of data to determine the completeness learning and to analyze the improvement students’ mathematical communication ability. The results of study showed that through the application of treffinger learning using a traditional game of congklak, then (1) mathematical communication ability of students reach the completeness learning, either individually and classical and (2) students’ mathematical communication ability had increased in the medium category by 65%.